2017
DOI: 10.1016/j.vetpar.2017.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of ten Haemonchus contortus isolates from different geographical origins towards acetone:water extracts of polyphenol-rich plants. Part 2: Infective L3 larvae

Abstract: This study explored the variation in susceptibility to acetone:water plant extracts between infective larvae (L) of ten Haemonchus contortus isolates from different geographical origin. The L of 10 different isolates were exposed either to the acetone:water extract of a temperate plant (Onobrychis viciifolia) or a tropical plant (Acacia pennatula) and were evaluated with the larval exsheathment inhibition assay (LEIA). The L of each isolate were incubated with different concentrations of each extract (0, 25, 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 25 publications
1
8
0
2
Order By: Relevance
“…Olmedo-Juárez et al [5] reported a larvicidal effect ( H. contortus ) greater than 70% at a dose of 150 mg/mL with an extract made from Acacia cochliacantha leaves and an LC 50 and LC 90 of 127.3 and 177.8 mg/mL, respectively. Also Chan-Pérez et al [14, 15] observed that H. contortus larvae after being exposed to an acetonic: aqueous extract of A. pennatula and O. viciifolia at concentrations of 600 μ g/mL showed evident lesions such as separation of the cuticle and the internal structures including the pharynx, bulb, and intestinal cells and when they were exposed to doses of 5000 μ g/mL the cuticle of the larvae was clearly swollen and the internal structures (pharynx, bulb, and intestine) were not distinguishable. The results also show that the larvicidal activity of the extract depends directly on the concentration dose.…”
Section: Resultsmentioning
confidence: 99%
“…Olmedo-Juárez et al [5] reported a larvicidal effect ( H. contortus ) greater than 70% at a dose of 150 mg/mL with an extract made from Acacia cochliacantha leaves and an LC 50 and LC 90 of 127.3 and 177.8 mg/mL, respectively. Also Chan-Pérez et al [14, 15] observed that H. contortus larvae after being exposed to an acetonic: aqueous extract of A. pennatula and O. viciifolia at concentrations of 600 μ g/mL showed evident lesions such as separation of the cuticle and the internal structures including the pharynx, bulb, and intestinal cells and when they were exposed to doses of 5000 μ g/mL the cuticle of the larvae was clearly swollen and the internal structures (pharynx, bulb, and intestine) were not distinguishable. The results also show that the larvicidal activity of the extract depends directly on the concentration dose.…”
Section: Resultsmentioning
confidence: 99%
“…A similar approach has been proposed for tropical regions. However, this search has also been prompted by a recent discovery: an H. contortus isolate from Mexico showing lower susceptibility to polyphenol-rich acetone: water extracts produced from leaves of plants commonly ingested by local sheep or goats [16,21,115]. These authors proposed that the H. contortus isolates obtained from animals browsing the tropical forest of Mexico showed some level of adaptation to plant polyphenols, possibly due to the constant exposure of the local GIN to the polyphenol-rich vegetation consumed by the hosts browsing this area.…”
Section: Tropical By-products Other Than Barkmentioning
confidence: 99%
“…El porcentaje del desenvaine (%D) y el de inhibición del desenvaine (%IDL) se determinaron con las siguientes fórmulas (28) : %D = Larvas L 3 con vaina larvas con vaina + larvas sin vaina × 100 %IDL = 100 − %D La inhibición de la EH y los resultados de IDL obtenidos para los diferentes extractos se analizaron con los respectivos modelos lineares generalizados (MLG) para evaluar las diferencias entre el control PBS y las diferentes concentraciones de extracto analizados. Los datos obtenidos de las incubaciones de PVPP de cada extracto se analizaron usando un diseño completamente al azar (MLG con comparaciones realizadas con el grupo control respectivo para cada extracto) (26) .…”
Section: Procesamiento De Datos Y Análisis Estadísticosunclassified